Constructed wetland-microbial fuel cells enhanced with iron carbon fillers for ciprofloxacin wastewater treatment and power generation. (October 2022) - Dai, Meixue; Wu, Yiming; Wang, Jie; Lv, Zhe; Li, Fei; Zhang, Yujia; Kong, Qiang
Abstract: In this study, the following three experimental devices were operated for 70 days for the treatment of ciprofloxacin pollutants in wastewater: constructed wetlands (CW), constructed wetland-microbial fuel cells (EG), and constructed wetland-microbial fuel cells with new iron-carbon fillers (TPFC). The water quality, power generation capacity, microbial community structure, and changes in the resistance gene qnrs were studied. The efficiency of removal of total phosphate in the TPFC (97.1% ± 2.5%) was significantly higher than that in the EG (51.6% ± 4.8%) and the CW (68.1% ± 2.9%). The efficiency of removal of ciprofloxacin was also significantly higher (TPFC: 91.2% ± 3.4%, EG: 82.1% ± 2.3%, and CW: 75.1% ± 5.6%) ( P < 0.05). The voltage of TPFC reached 300.16 ± 12.12 mV, which was apparently greater than that of EG (180.36 ± 16.73 mV) ( P < 0.05), possibly because of the higher abundance of microorganisms such as Burkholderiaceae, Hydrogenophaga, and Proteobacteria . There were more copies of the resistance gene qnrs (TPFC: 7.74/μL, EG: 5.52/μL, and CW: 2.65/μL), which may be associated with stronger resistance; therefore, the efficiency of removal of ciprofloxacin was higher in the TPFC. TPFCs are a promising way to remove ciprofloxacin in wastewater. Highlights: Porous iron-carbon material was added to TPFC anode reactions. Better electrochemical performance was noted in TPFC over a 70-day period. Removal of CIP and TP was significantly improved in the TPFC ( P < 0.05). Ciprofloxacin exhibits broad-spectrum lethality against microorganisms. The TPFC had more resistance genes and microorganisms with better tolerability.